THE EFFECT OF INSTITUTIONAL OWNERSHIP, INDEPENDENT BOARD OF COMMISSIONERS, AUDIT COMMITTEE, AUDIT QUALITY, AND CORPORATE SOCIAL RESPONSIBILITY (CSR) ON TAX AVOIDANCE - Bayhaqi, Dzawil Al (Tax Accounting Applied Journal, 2024)
The problem in this study is caused by fluctuations in the tax ratio, which tends to decrease due to differences in interests between the government and corporate taxpayers so that indications of tax avoidance appear. This study aims to find empirical evidence of factors affecting tax avoidance, such as institutional ownership, independent board of commissioners, audit committee, audit quality, and CSR. The measurement used in tax avoidance uses ETR. The study population used manufacturing companies listed on the IDX in 2019-2021. Sample determination using purposive sampling method and secondary data. The study results of variables of institutional ownership, independent board of commissioners, audit quality, and CSR do not affect tax avoidance, while the audit committee can affect tax avoidance.